Exploring students’ articulation of value in a social research methods class: Towards a phenomenography of value making - Guglietti, Maria (Teaching and Learning Inquiry, 2015)
This study describes journalism students’ value making of social research methods, such as sampling, data gathering strategies and quantitative and qualitative data analysis, by using a mixed-method approach to analyze 260 written reflection assignments. In their reflections, 26 student participants assessed the value of their new knowledge of social research methods on ten different occasions throughout the term. The qualitative analysis consisted of two stages: a content analysis and an analysis of students’ collective experience of value making (phenomenographic approach). The findings of the content analysis showed that students generally value knowledge that is seen as useful and familiar from the perspective of trainee practitioners (professional standpoint). A focus on students’ collective experience showed that value making happens when students adopt a standpoint from where to judge new knowledge and make connections between new and past knowledge and experience. Weak connections may lead students to disregard new content. The analysis of connections showed that students either reproduce the connections made by the instructor in class (performative connection) or make an original link with present and past experiences and knowledge (original connection). Performative connections produce general statements of value making, while concrete value making happens when students explicitly integrate and transfer knowledge to produce original connections with past and present personal or professional learning and experience.